Exploring Senior High School Students’ Perceptions of Multimodality in ELT - Endah Luthfiyah; Devi Mulatsih (Yayasan Visi Intan Permata, 2025)
The implementation of multimodal approaches in English Language Teaching (ELT) has been increasingly recognized for its ability to enhance student engagement and comprehension. However, few studies have explored how students perceive specific multimodal elements—such as audio/video, visual design, voice and facial expression, gesture, and spatial position—in authentic classroom contexts, particularly at the high school level in Indonesia. This study aims to investigate high school students’ perceptions of the use of multimodality in ELT also the benefits and challenges they experience from each element. This study used a qualitative descriptive research design, that data were collected from 30 senior high school students through closed- and open-ended questionnaires. Thematic analysis was used to interpret both quantitative and qualitative responses. The results showed that the most preferred elements of multimodality were audio/video, followed by visual design, voice and facial expression, movement, and spatial position. The benefits felt by learners were that it improved comprehension and helped them to focus in class. However, some challenges were also reported, including technical constraints (e.g., internet instability, unclear audio), fast audio delivery, and excessive teacher gestures, which disrupted students' concentration. This study emphasizes that a carefully designed multimodal approach can create a more inclusive and engaging learning environment. Implications for educators include strategic integration of multimodal elements, professional development in digital literacy and infrastructure improvements. Future research is recommended to explore the direct impact of multimodal strategies on learning outcomes across different contexts.